Export market orientation, organizational knowledge and export market performance: the mediating effect of organizational innovation - Rahil, Mousa (2015)
Arab markets present significant opportunity for Malaysian exporters to grow their sales and profits. Innovation is crucial in creating values and sustainable competitive advantage. However, there are still much to explore on the role of organizational innovation. There is lacking of literature that has incorporated organizational innovation as a mediating variable between export market orientation and organizational knowledge with export market performance. The issue between market orientation and organizational performance has been focused of study over the past three decades. Literature reviews that numerous research works on organizational innovation affecting export performance, have been inconclusive, inconsistent, and characterized by low levels of explanation. Hence, it is crucial to exporters to identify factors influencing performance. This is a quantitative study. The population was selected from the 2011 Federation of Malaysian Manufacturers (FMM) directory. A total of 107 respondents responded to the survey questionnaire distributed to manufacturers that have been exporting for 5 years and above were used in testing the hypotheses formulated. This study found that there is a significant direct relationship between export market orientation and export market performance at p<0.05. Similarly, organizational knowledge was found to be significantly related to export market performance at p <0.05. Organizational innovation was found to have direct influence on export market performance at p<0.001. Finding showed that organizational innovation mediates the relationship between export market orientation and organizational knowledge with export market performance at p<0.05. This implies that in order to enhance performance, exporters should also emphasize on organizational innovation, besides organizational knowledge and export market orientation.